2014
DOI: 10.1039/c4ra05814c
|View full text |Cite
|
Sign up to set email alerts
|

Polypropylene–graphene – a nanocomposite that can be converted into a meta-material at desired frequencies

Abstract: Meta material (having negative dielectric constant) characteristics were observed in polymeric nanocomposites consisting of polypropylene and graphene. By varying the concentration of graphene the frequency at which the meta material was converted into a positive dielectric material was controlled. At percolation thresholds the dielectric constant had maximum negative values at low frequencies and high positive dielectric constant values at high frequencies. The dielectric measurements reveal that low concentr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
10
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(14 citation statements)
references
References 38 publications
2
10
0
Order By: Relevance
“…Nanocomposites of iPP/graphene show σ (AC) ca. 10 −4 S/cm [20], using 30 wt % or higher of graphene. However, the fabrication of iPP/MWCNT with 10 wt % of fillers is important because a high loading of filler can reduce the mechanical properties of PP/CNT [22].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Nanocomposites of iPP/graphene show σ (AC) ca. 10 −4 S/cm [20], using 30 wt % or higher of graphene. However, the fabrication of iPP/MWCNT with 10 wt % of fillers is important because a high loading of filler can reduce the mechanical properties of PP/CNT [22].…”
Section: Resultsmentioning
confidence: 99%
“…The type of electrical behavior is also dependent, in turn, on the MFI of the iPP and on the fabrication method. In a previous report [20], the dielectric constant behavior was studied as a function of the graphene content at different frequencies. It was shown that an amount of 30 wt % or 40 wt % of graphene was needed to obtain a negative dielectric constant and the crossover from negative to positive was ca.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Negative real permittivity has been observed for some polymer nanocomposites that include carbon-based nanoparticles [1]. Ramasamy et al reported, for example, that it is possible to observe a high negative real permittivity when the graphene addition reaches a critical concentration in polypropylene (PP) [3]. From this point of view, the present work was focused on producing novel polymer-based composites having negative real permittivity.…”
Section: Introductionmentioning
confidence: 96%